Turkish Islamic Actors in Africa : the Case Study of Hayrat Vakfi in Niger - Abdoulaye, Ibrahim Bachir; Institute of African Studies (University of Bayreuth African Studies Working Papers, 2024)
In the last two decades, Turkish Islamic movements have extended their influence to Niger, a predominantly Muslim state. Diverse Turkish Islamic movements, such as the Nur Cemaati, Süleymancı Cemaati, and Erenköy Cemaati, are actively engaging in Islamic education through Qur'anic schools and education centers in Niger. This paper, specifically, delves into the activities of the Hayrat Vakfi (Hayrat Foundation), a branch of the Nur Cemaati (Nur movement). The central thesis of this paper asserts that the presence of Turkish Islamic actors has initiated a "silent transformation" within Niger's Islamic landscape. To comprehend this phenomenon, the paper addresses three key inquiries: (a) The internal socio-political and economic dynamics of Turkey that drove Turkish Islamic movements toward internationalization, (b) The expansion strategies employed by Hayrat Vakfi for the dissemination of its Islamic teachings, and (c) The implications of its presence in the transformation of Niger's Islamic landscape. Methodologically, this research employs a single case study approach with ethnographic and historical analysis. Existing scholarship on Turkish actors in Africa has predominantly focused on topics such as humanitarian aid, trade, and diplomacy. Therefore, this study aims to expand the scope of scholarly exploration to encompass other dimensions of Turkish presence in the African continent.
Keywords: Islam; Níger; Hayrat Vakfi; Nur movement; Turkey